CoroEval: a multi-platform, multi-modality tool for the evaluation of 3D coronary vessel reconstructions - Schwemmer, Chris; Forman, Christoph; Wetzl, Jens; Maier, Andreas; Hornegger, Joachim (Physics in Medicine and Biology, 2014)
With default settings, measurements are taken at 1 mm intervals along the vessel centreline and from 10 different angles at each measurement point. This allows for outlier detection and noise-robust measurements without the burden and subjectivity a manual measurement process would incur. Graphical measurement results can be directly exported to vector or bitmap graphics for integration into scientific publications. Centreline and lumen segmentations can be exported as point clouds and in various mesh formats. We evaluated the diameter measurement process using three phantom datasets. An average deviation of 0.03 +/- 0.03 mm was found.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.coroev
Keywords: medical imaging; coronary vessels; evaluation; software